Modificação das posturas dos simuladores antropomórficos voxel de referência Adult Male (AM) e Adult Female (AF) para cálculo de coeficientes de conversão de dose - Galeano, Diego Castanon (2016)
Establish limits to the exposure of the population to various ionizing radiation sources is crucial to prevent occupationally exposed individuals and the public, to their deleterious effects. In computational ambit, it is necessary that different exposure scenarios are simulated in order to obtain the dose coefficients (CCs), which relate physical dosimetric quantities - as absorbed dose, Fluency or Kerma Air - with limiting quantities - as equivalent and / or effective dose. Under certain exposure conditions, the individual's posture is not always the same, and the scenario shall be described as realistic as possible. In this work, the AM (Adult Male) and AF (Adult Female) anthropomorphic reference phantom of ICRP publication n° 110 had their postures modified from supine posture (standing) to sitting posture. The change of posture was performed through of a subroutine written in the Visual Monte Carlo code (VMC) to rotate the thigh region of the phantom and position it between the region of the leg and torso. The ScionImage software was used to reconstruct and smooth the knee and hip contours in a sitting posture phantom, and for 3D visualization of phantom was used VolView software. After this step the MCNPX radiation transport code was used for the calculation of fluence-to-dose conversion coefficients (CCs) to six irradiation geometries: AP, PA, LLAT, RLAT, ROT and ISO, recommended by ICRP. The results were compared between the phantoms in standing and sitting postures, for both sexes, in order to assess differences in scattering and absorption of radiation in different postures. The results show significant differences of up to 100% in the equivalent dose conversion coefficients of organs in the pelvic region, 79 % in organs with distribution in the whole body (such as skin, muscle, lymph nodes, bone marrow and trabecular bone) and a difference of 27% to effective dose conversion coefficients. Moreover in order to conduct a comparative study between two types of simulators, was estimated CCs equivalent and effective dose of adult male hybrid simulators, UFHADM, and female, UFHADF, in a sitting posture, and compared to the AM and AF simulators, also in the sitting posture, where it was observed significant difference in energies below 0.05 MeV. This study demonstrated the feasibility of using anthropomorphic phantoms in the sitting posture to represent more realistic postures and can be used in studies in medical and occupational dosimetry. This study demonstrated the feasibility of using anthropomorphic simulators reference in the seated position to represent more realistic positions can thus be used in studies in medical and occupational dosimetry as well as the importance of developing as realistic simulators as possible to dose estimation as faithful as possible in different irradiation scenarios.